Comprehensive approaches to design efficient gRNA for SDN1-CRISPR/Cas9 genome editing in wheat - Singh, Tushadri; Mamrutha, H. M.; Singh, Rajender; Jaiswal, J. P.; Wadhwa, Zeenat; Kumar, Rakesh; Singh, Omvir; Ahlawat, O. P.; Tiwari, Ratan (Frontiers in Genome Editing, 2025)
BackgroundCRISPR/Cas9 technology has gained popularity due to its efficient, widely applicable, and relatively easy genome editing. Furthermore, the removal of regulation on site-directed nuclease1- (SDN1) and SDN2-developed products in many countries has made it a more revolutionary technology for adoption in crop improvement. Designing accurate guide RNA (gRNA) is the initial and most crucial step that decides the success of the editing. Although the gene editing technique is widely used in crops, a detailed and comprehensive method for designing efficient gRNA in wheat is still lacking. By virtue of wheat being a hexaploid crop and having a large genome size with repetitive DNA, a tailor-made strategy for designing the gRNA is crucial.ResultThe manuscript explains the comprehensive strategies and methods for efficient gRNA designing by considering the physical and structural expression of the target gene in the genome and explains the on-target and off-target effects of gRNA for its precise editing through the CRISPR/Cas9-mediated SDN1 method of genome editing in wheat.ConclusionThe present manuscript is first of its kind to address the holistic approach, starting from efficient gene selection, gRNA designing, and post-gRNA designing issues like gRNA stability, binding efficiency, and functionality for SDN1-CRISPR/Cas9 genome editing in wheat. This manuscript will be a ready reference for wheat researchers designing effective gRNA for wheat improvement to meet future food demand.